Clinician Versus Veteran Ratings on the Mayo-Portland Participation Index in Veterans With a History of Mild Traumatic Brain Injury. Issue 1 (January 2015) - McCulloch, Katie; Pastorek, Nicholas J.; Miller, Brian I.; Romesser, Jennifer; Linck, John; Sim, Anita H.; Troyanskaya, Maya; Maestas, Kacey Little; Caplan, Bruce; Bogner, Jennifer; Brenner, Lisa
<x xml:space="preserve">Abstract</x> Background: The Department of Veterans Affairs is encouraging administration of the Mayo-Portland Adaptability Inventory–4 Participation Index (M2PI) to identify long-term psychosocial outcomes of Operation Enduring Freedom (OEF), Operation Iraqi Freedom (OIF), and Operation New Dawn (OND) Veterans with a history of traumatic brain injury (TBI). Objective: To evaluate clinician and Veteran interrater reliability and how response validity influences M2PI item ratings. Participants: A total of 122 OEF/OIF/OND Veterans who reported a history consistent with mild TBI during deployment and were referred for neuropsychological evaluation following Comprehensive TBI Evaluation. Design: Interrater reliability study. Main Measures: M2PI; Minnesota Multiphasic Personality Inventory–2 Symptom Validity Scale (FBS). Results: Veterans reported greater perceived restrictions than clinicians across all M2PI items and total score. Interrater correlations ranged from rs = 0.27 (residence) to rs = 0.58 (money management) across items, with a total score correlation of rs = 0.60. When response bias was indicated, both Veterans and clinicians reported greater participation restrictions than those reported by Veterans without evidenced response bias. Conclusion: Low interrater correlation is consistent with previous findings. As ratings of clinicians and Veterans should not be interpreted as equivalent, documenting the rater's identity is important for interpretation. Using objective indicators of functional outcome may assist clinician raters, particularly when self-report may be biased.